A circular planar frequency diverse array for monostatic radar applications. Issue 9 (2nd September 2019) - RastgarKisomi, S.; Mohseni Armaki, S. H.; Rashidi, A. J.; Fallah, M.
ABSTRACT: Frequency diverse arrays (FDAs) with scanning features have recently been of interest to radar researchers. Different frequencies with different patterns applied to the properly arranged array elements lead to the range-angle dependent beampattern. In this paper, a monostatic radar system in which the transmitter is an FDA and the receiver is a phased array is proposed, with both of which being arranged in circular planar arrays. The elements of the FDA transmitter are located at several concentric rings. The elements frequency in each ring is the same and the frequency difference between the two adjacent rings is constant. The radius of each ring is proportional to the half-wavelength of the same ring. The presented structure produces a periodic range-angle dependent beampattern. By applying a non-uniform inter-ring frequency offset, a non-periodic beampattern is radiated. In the transmitter and receiver mode, the transmitted signal to the target is reﬂected back to the phased array receiver. Similar to the transmitter, the receiver is composed of several concentric rings located after the last ring of the transmitter and the radius of each ring is proportional to the half-wavelength of central frequency.